Juvenile Justice Systems in Europe – Reform developments between justice, welfare and ‘new punitiveness’1 - DÜNKEL, FRIEDER (Kriminologijos studijos, 2014)
This article evaluates youth justice policies and practice in Europe from a comparative perspective. The focus is on tendencies in youth justice legislation and on the sentencing practice of prosecutors and judges in youth courts. Attention is also paid to the traditional ‚welfare‘ and ‚justice‘ models of youth justice and how they have become intertwined in modern European practice. Against this background of a range of old and newly prominent ideas combined withsomewhat fractured models, one can identify a number of reform strategies. Despite obvious and undeniable national particularities, there is a recognisable degree of convergence among the systems in Western, Central and Eastern Europe. Even if reform developments in juvenile justice legislation do not confirm a ‚punitive turn‘ it would be possible that sentencing practices in some or many countries follow the ‚getting tough‘-approach in order to fulfill public demands on reacting towards juvenile delinquency by more severe sanctioning.Key Words: Juvenile justice, juvenile delinquency, comparative perspective, youth justice models, age of criminal responsibility, young adults, restorative justice.